1995
DOI: 10.1002/dvg.1020160211
|View full text |Cite
|
Sign up to set email alerts
|

Cell interactions in testis development: Overexpression of c‐mos in spermatocytes leads to increased germ cell proliferation

Abstract: Possible functions of the c-mos proto-oncogene during spermatogenesis were investigated through perturbations of its expression in transgenic mice. Two promoters, one from the pre-meiotic male germ cell-specific mouse phosphoglycerate kinase 2 gene, and the other from the post-meiotic male germ cell-specific rat RT7 gene were used to direct expression of c-mos. Northern blot analysis of testis RNA from transgenic PGK-c-mos mice indicated elevated levels of c-mos RNA in spermatocytes and spermatids compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Western Blot Analysis-Elutriated rat germ cells were prepared according to Higgy et al (37). Elutriated fractions, of ϳ90% purity, were obtained for elongated spermatids, round spermatids, and spermatocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot Analysis-Elutriated rat germ cells were prepared according to Higgy et al (37). Elutriated fractions, of ϳ90% purity, were obtained for elongated spermatids, round spermatids, and spermatocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Spermatocytes and spermatids were obtained by centrifugal elutriation of SD rat spermatogenic cells as described previously (30,41), and RNA was isolated as described above. RNA samples were analyzed by Northern blotting/hybridization using Duralon-UV membranes (Stratagene) and indicated random-primed probes as described (39).…”
Section: Rna Analysismentioning
confidence: 99%
“…The odf27 gene is abundantly transcribed in spermatids and translated in elongating spermatids. We demonstrated that the odf27 promoter confers spermatidspecific expression (29,30) and that it is activated by the spermatid-specific Crem transcription factor (31). Analysis of the predicted Odf27 amino acid sequence revealed two putative domains.…”
mentioning
confidence: 93%
“…A single cell suspension was obtained by repeated pipetting of tubules and filtration through a 120-m nylon mesh. Pachytene spermatocytes, round spermatids, and elongating spermatids were then isolated by centrifugal elutriation (33,34) of released germ cells.…”
Section: Methodsmentioning
confidence: 99%